Impact of spring warming on sowing times of cereal, potato and sugar beet in Finland - KAUKORANTA, T.; HAKALA, K. (Agricultural and Food Science, 2008)
Historical data were used to determine if the warm springs experienced in recent decades have influenced time of sowing of spring cereals (barley, wheat and oats), potato and sugar beet in Finland. The start of the thermal growing season was used to represent all climatic factors affecting sowing time. Regional anomalies in sowing and start of growing season were computed for the years 19652007. The start of the growing season was 22.8 days earlier per decade, with a steeper increase since 1980. Sugar beet sowing advanced 2.5 (since 1980 5.2) and potato planting 3.4 (since 1980 4.5) days per decade, more than expected solely due to earlier starts to the growing season. Sowing of spring cereals advanced 0.6, 0.7 and 1.7 days per decade in the east, north and west respectively (since 1980 1.0, 1.9 and 3.1), with statistically significant trend (p < 0.01) in the west. Earlier sowings can be largely explained by warmer springs, but the trend was not as steep as that for the growing season. This has however not led to increased temperatures during early vegetative phases and thus faster development and increased drought or pest risk, which would have reduced the positive effects of earlier sowing on yield potential. Earlier sowing detected in the west can be explained by changes in spring temperatures, but may also result from economic and technological development. Farmers seem to have adequately adjusted their field activities to the changes in spring temperatures.;